Determinants of intrinsic capacity among older adults in low- and middle-income countries: A scoping review - Tang, Linxi; Binti Rasudin, Nur Syahmina; Dong, Yuan; Yusuf, Azlina (Belitung Nursing Journal, 2025)
Background: Intrinsic capacity (IC), as defined by the World Health Organization (WHO), represents the composite of an individual’s physical and mental capacities and forms a cornerstone of the healthy aging framework. Understanding its determinants is essential for designing effective interventions, particularly in low- and middle-income countries (LMICs) where population aging is accelerating amid limited resources and fragmented health systems. Mapping these determinants supports evidence-based strategies that enhance functional ability and resilience among older adults. Objective: This scoping review aimed to systematically map and categorize the determinants of IC among older adults in LMICs, providing an evidence base to inform nursing practice and policy development. Methods: Following PRISMA-ScR guidelines, four databases (Web of Science, PubMed, Scopus, and EBSCOhost) were searched for peer-reviewed studies published between January 2015 and April 2025. Data were synthesized thematically and classified into four determinant domains. Results: Thirty-six studies met inclusion criteria. The determinants of IC were grouped into four domains: (1) sociodemographic (age, gender, education, marital and economic status, living arrangement, residence); (2) biological, physiological, and disease-related (chronic diseases, multimorbidity, body mass index, frailty, polypharmacy, biomarkers); (3) behavioral and lifestyle (physical activity, diet, smoking, alcohol use, sleep, health-seeking behavior); and (4) environmental (housing quality, social participation, community support, healthcare accessibility). Advancing age, chronic disease burden, frailty, and social isolation were linked to reduced IC, while education, good nutrition, physical activity, and supportive environments were protective. Conclusion: Intrinsic capacity in older adults from LMICs is shaped by interrelated social, biological, behavioral, and environmental factors. For nursing and health policy, these findings emphasize the need to shift from disease-centered to proactive, function-oriented care. Integrating IC monitoring into routine nursing practice, promoting health literacy, and creating age-friendly environments are critical for sustaining IC and promoting equitable, healthy aging. Findings from this review may serve as a valuable reference for practitioners and policymakers in LMICs. Registry: Open Science Framework (OSF) [10.17605/OSF.IO/HQ6PG]